Factors influencing social shopping intention: the mediating role of trust - Abu Bakar, Nur Hasanah Baqiah (2021)
Social commerce is one of the essential ideas and has been connected people in recent years. Social media has become a significant instrument for scattering data about organizations, merchandise, and services. Moreover, researchers have perceived the capability of Internet-based correspondence innovations for improving network research since a long time ago. Therefore, this study aimed to study the role of trust as a mediator in the relationship between perceived quality of information, perceived quality of the system, perceived quality of service and social shopping intentions. 391 students from Universiti Utara Malaysia were randomly selected to respond to the survey. The questionnaire consisted of 20 items covering selected factors PIQ, PSQ, PSvQ, trust and SSI. The data collected for tested and analysed. The results of this study confirm perceived information quality, perceived system quality, perceived service quality positively related to the trust as mediator and significant to the social shopping intention. Finally, this study contributes to the theory of the Socio- Cognitive Theory because of the implementation of trust can effectively improve intention to buy and ultimately perceived information quality, perceived system quality, perceived service quality. In addition, this study also looks at the implications as well as discusses the recommendations of future studies.